Succession : mastering the make or break process of leadership transition - Tichy, Noel M. (Portfolio, 2014)
"Starting out at GE, where he headed up the company's leadership institute and revamped the leadership pipeline under Jack Welch, Noel Tichy has served as a trusted advisor on management succession to such leading companies as Royal Dutch Shell, Nokia, Intel, Ford, Mercedes-Benz, Merck and Caterpillar. Now Tichy draws on decades of hands-on experience working with CEOs and boards to provide a framework for building a smart, effective transition pipeline, whether for a multi-billion dollar conglomerate, a family business, a small start-up, or a non-profit. Through revealing case studies like Hewlett Packard, IBM, Yahoo, P&G, Intel, and J.C. Penney, he examines why some companies fail and others succeed in training and sustaining the next generation of senior leaders. He highlights the common mistakes that can generate embarrassing headlines and may even call an organization's survival into question, and reveals the best practices of those who got it right. Tichy also positions leadership talent development and succession where they belong: at the top of every leader's agenda. "--